Answer:
Step-by-step explanation:
20%
Answer:
So first lets find g(-1)
so we plug in the answers:
-2 * -1 ^2 -4
-2*1-4 = -2-4 =
-6
Now lets solve for f(-2)
-2^2-3
4-3=1
-6+1 = 5
3*5 = 15
Im getting answer of 15 but it shows -15 or something, so I dont know if I got it wrong or if its like a dash then the answer.
Answer:
1st, 3rd, 4th, 2nd
Step-by-step explanation:
Ten and seventy-three hundredths
Step-by-step explanation:
3 and 4.
because the sum of the smaller two sides of a triangle have to be less than or equal to the 3rd larger side.